Institutional Contradictions of the French state as Shareholder. Issue 3 (7th April 2020) - Girard, Carine; Gates, Stephen
Abstract : Purpose: This paper aims to demonstrate that state shareholders are confronted with contradictory logics leading to institutional contradictions that activist shareholders can exploit. The competing logics of the state as shareholder and their impact on corporate governance and shareholder activism offer fertile grounds for research advances in Coordinated Market Economies (CMEs). Design/methodology/approach: Through an extensive literature review of state ownership, institutional contradictions and shareholder activism, this paper analyzes two case studies involving the French State as shareholder. Findings: In the French context, these two cases illustrate how institutional contradictions result in opportunities for shareholder activism. By focusing on the institutional contradictions of the state shareholder, this investigation suggests a need for experimental research to observe how shareholder activists adapt to each institutional change in CMEs. This experimentation can help policymakers to avoid creating additional conditions that shareholder activists can exploit. Research limitations/implications: This focuses only on France and its state shareholdings. To generalize results, studies of other CMEs and state shareholders are needed. Practical implications: Policymakers should consider all legislative proposals for their potential to deviate from corporate governance practice by experimenting with them in a laboratory setting. Shareholder activists can compare state shareholders' actions against the state's legislation to emphasize institutional contradictions that counter minority shareholders' rights. Originality/value: This research is the first to analyze how the state as shareholder can exploit its competing logics to resist against shareholder activism and support management or to become itself a shareholder activist.